Analisis Spasial Tingkat Bahaya Erosi pada DAS Bone-Gorontalo Tahun 2013 dan 2023 Menggunakan Metode Usle - Yusfriandi Dwi Ariesna; Frandika K. Toiyo; Rahmawati A. Damiti; Fitryane Lihawa; Iswan Dunggio (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research aims to analyze the erosion hazard level in the Bone-Gorontalo River Basin (DAS) using the Universal Soil Loss Equation (USLE) for the years 2013 and 2023. The data utilized in this study is secondary, consisting of official documents, scientific articles, and information from statistical agencies. A qualitative descriptive research method is applied to provide an in-depth overview of changes in soil erosion conditions. The analysis results show that the area classified as very light (Class I) increased from 3,873.84 hectares in 2013 to 5,404.92 hectares in 2023, reflecting an improvement in soil conditions. Although there was an increase in the light category (Class II), areas in the moderate (Class III) and heavy (Class IV) categories also saw an increase, indicating a need for further intervention. The total annual erosivity decreased from 1,180.70 to 766.65, indicating a positive response to climate change and improved land management. This study recommends more intensive conservation actions to reduce erosion risks, especially in areas that remain vulnerable.